Optimalisasi Penentuan Lokasi Rumah Pompa Air dengan Metode P-Center dalam Meningkatkan Efisiensi Distribusi Pelanggan Air PDAM - Usada, Untung (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
In carrying out the goals of PDAM Surabaya, there are several efforts that have been made by the Company, starting from processing river water into clean water that is ready for use to setting up the distribution network. Determining the distribution location has an important role in the network distribution management system. This research aims to determine the location of the Pump House which is a place for distributing reservoir water. By using the P-Center method in the hope of finding an effective and efficient Pump House location. Data collection used in this research used an observation and interview process. The research sample was carried out in a Zone 5 area in the zone division of PDAM Surya Sembada, Surabaya City. To determine the location, the P-Center mathematical model is used. The results of this research show that the optimal location for placing a water distribution pump house is in subzone 526 pump house location serving 5,732 customers and 513 serving 5,610 customers. So with the 2 locations found we can serve as many as 11,324 customers.